Detección del Nodo Oculto en Escenarios LAA WiFi - Campos Yucailla, Pablo; Hernández, Angela; Valdovinos, Antonio (Jornada de Jóvenes Investigadores del I3A, 2018)
This paper presents a method for the detection of hidden nodes and the estimation of the traffic load of the neighboring cell in heterogeneous networks Licensed Assisted Access (LAA) / WiFi. The method uses the statistical distribution of the Channel Quality Indicator (CQI) metric used into LTE networks allowing to obtain the described objectives.